Plastin increases cortical connectivity to facilitate robust polarization and timely cytokinesis - Ding, Wei Yung; Nédélec, François (The journal of cell biology, 2017)
Ding et al. characterize the function of the F-actin bundling protein plastin in the Caenorhabditis elegans zygote. They demonstrate that plastin is important for optimal connectivity in the cortical actomyosin network that drives large-scale contractile processes such as polarization and cytokinesis., The cell cortex is essential to maintain animal cell shape, and contractile forces generated within it by nonmuscle myosin II (NMY-2) drive cellular morphogenetic processes such as cytokinesis. The role of actin cross-linking proteins in cortical dynamics is still incompletely understood. Here, we show that the evolutionarily conserved actin bundling/cross-linking protein plastin is instrumental for the generation of potent cortical actomyosin contractility in the Caenorhabditis elegans zygote. PLST-1 was enriched in contractile structures and was required for effective coalescence of NMY-2 filaments into large contractile foci and for long-range coordinated contractility in the cortex. In the absence of PLST-1, polarization was compromised, cytokinesis was delayed or failed, and 50% of embryos died during development. Moreover, mathematical modeling showed that an optimal amount of bundling agents enhanced the ability of a network to contract. We propose that by increasing the connectivity of the F-actin meshwork, plastin enables the cortex to generate stronger and more coordinated forces to accomplish cellular morphogenesis.